SRI Momentum : Examining a socially responsible momentum strategy - Laiho, Antton (My University, 2022)
ESG-factors are theorized in earlier literature to improve financial performance of investment strategies. This paper examines the combination of these two phenomena together in the form of ESG-momentum and investigates the driving forces behind the possible positive returns provided by the ESG-momentum strategy. This paper’s significance lies in the insights it brings into the field of ESG-rating related studies and socially responsible investing An ESG-momentum portfolio is formed by ranking the absolute value changes of ESG-ratings received by companies of the S&P500 index. These portfolios are then measured with CAPM and multi-factor metrics, and the drivers of these returns are examined. The regression testing conducted concludes that sorting stocks in the S&P500 index with ESG- ratings does not provide excess positive returns during the period of 2010-2020. It’s also concluded that the portfolios do not have high levels of exposure to the factors of the Fama & French multi-factor models, apart from beta. With the null hypothesis true, this paper offers contributions to ever growing literature about socially responsible investing and the strategies that it includes. Additional value brings the finding of levels of beta-exposure, which can in future be used to study possible implementations in strategies involving hedging.

ESG-tekijöiden teoretisoidaan aiemmassa kirjallisuudessa parantavan sijoitusstrategioiden tuottomahdollisuuksia. Tästä syystä tässä työssä tarkastellaan näitä kahta ilmiötä yhdessä ESG- momentumin muodossa ja pyritään selvittämään, että tuottaako tämä strategia ylituottoa, sekä että mistä tämä tuotto johtuu. Tämä työ tarjoaa merkittävää lisätietoa vähän tutkittujen ESG- tekijöiden piiriin sekä ESG-momentumin että yleisellä tasolla vastuullisen sijoittamisen muodossa. Portfolio luodaan sijoittamalla yhtiöt arvojärjestykseen absoluuttisten ESG-arvojen perusteella S&P500 indeksissä. Absoluuttisten arvojen muutoksia käytetään momentum -portfolion muodostamiseen ja näitä portfolioita tarkastellaan yksi- sekä moniulotteisten taloudellisten suoritusmittareiden avulla. Regressiomallien löydökset viittaavat siihen, että ESG-arvojen perusteella järjestäminen ei tuota tilastollisesti merkittävää ylituottoa, eikä strategian avulla luodut portfoliot ole altistuneita Faman ja Frenchin viiden tai kolmen tekijän mallin tekijöille, beta poissulkien. Nollahypoteesin jäädessä voimaan tämä työ tarjoaa merkittävää lisätietoa alati kasvavaan kirjallisuuteen vastuullisesta sijoittamisesta ja sen mukana tulevista sijoitusstrategioista. Lisäksi lisäarvoa tuottaa että portfolioista löytyi beta-altistumista. Tätä voidaan jatkossa käyttää lisätutkimuksissa esimerkiksi työkaluna suojautumisstrategioissa markkinoita vastaan.
Keywords: social responsibility; investements; strategies; portfolios; investment activities; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance